2021
DOI: 10.1021/acs.jpcb.1c06636
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Elucidation of Molecular Picture of Water–Choline Chloride Mixture

Abstract: Choline chloride (ChCl) is a component of several deep eutectic solvents (DESs) having numerous applications. Recent studies have reported manifold promising use of aqueous choline chloride solution as an alternative to DES, where water plays the role of the hydrogen-bond donor. The characteristic physical properties of the DESs and aqueous DES originate from the "inter-" and intraspecies hydrogen-bond network formed by the constituents. However, a detailed molecular-level picture of choline chloride and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…The quantitative difference between water content that corresponds to a transition to a dilute aqueous solution obtained by Kumari et al [ 286 ] and Sapir et al [ 292 ] could be explained by the differences in the water models used in these works. Sarkar et al [ 300 , 301 ] confirmed the results obtained by Kumari et al [ 286 ] and Sapir et al [ 292 ] and investigated changes in water structure with the increase in the fraction of reline [ 300 ] and pure ChCl [ 301 ]. They showed that in the presence of reline, water–water contacts are replaced with contacts between water and urea molecules and chloride anions, which affects water structure significantly.…”
Section: Main Directions Of Investigationssupporting
confidence: 55%
“…The quantitative difference between water content that corresponds to a transition to a dilute aqueous solution obtained by Kumari et al [ 286 ] and Sapir et al [ 292 ] could be explained by the differences in the water models used in these works. Sarkar et al [ 300 , 301 ] confirmed the results obtained by Kumari et al [ 286 ] and Sapir et al [ 292 ] and investigated changes in water structure with the increase in the fraction of reline [ 300 ] and pure ChCl [ 301 ]. They showed that in the presence of reline, water–water contacts are replaced with contacts between water and urea molecules and chloride anions, which affects water structure significantly.…”
Section: Main Directions Of Investigationssupporting
confidence: 55%
“…Only ∼1 % of the mono‐coordinated water molecules show binding with the choline (red bar). This is since there is less chance for choline molecule to reside in the coordination sphere of a central water molecule owing to its inherent bulky size and due to increased wt % of ChCl, there is an exchange between water and chloride ions since the hydration strength of the chloride ions is greater than water as observed by Sarkar et al [11] …”
Section: Resultsmentioning
confidence: 93%
“…The numbers of different constituents are provided in Table S1 of supporting information. This stepwise solvation method is widely used in building multicomponent mixtures and has been previously used in several other studies [11,19,47,48] . We have generated five different systems for this investigation by varying the concentration of choline chloride.…”
Section: Modeling and Simulation Detailsmentioning
confidence: 99%
“…A different approach was also contemplated for designing a sustainable VOC trapping system, which is a hybrid material of DES and β-cyclodextrin . A molecular simulation study of reline-water showed the overall growth of interspecies association with increasing concentrations of choline chloride …”
Section: Introductionmentioning
confidence: 99%
“…37 A molecular simulation study of reline-water showed the overall growth of interspecies association with increasing concentrations of choline chloride. 38 Although the above experimental studies have indicated efficient absorption of VOCs in DESs, the molecular picture is still lacking. To fabricate a more efficient DES for the absorption of different VOCs, it is important to investigate the underlying molecular interactions for the absorption.…”
Section: Introductionmentioning
confidence: 99%